Optimization of the Process for Slow-Release Urea Fertilizer with Water Absorption Based on Response Surface Methodology - Yan Li; Yu Ma; Yan Wang; Fan Chang; Jiakun Dai (Applied Sciences, 2024)
Fertilizers that release nutrients slowly can provide crops with consistent nutrients, while soils with good water-holding capacity can alleviate the impact of droughts on crops. Sodium alginate/carboxymethyl starch sodium/polydopamine/urea (SCPU) is a new kind of slow-release fertilizer with water absorption property. In this study, the Box–Behnken response surface methodology (RSM) was used to reveal the effects of concentrations of sodium alginate, carboxymethyl starch sodium, urea, calcium chloride and dopamine on the encapsulation efficiency and water absorption of SCPU. The results show that the optimum preparation conditions to obtain the highest level of encapsulation efficiency (89.27%) and water absorption (167.05%) are 2.2% sodium alginate, 5% carboxymethyl starch sodium, 30% urea, 1.9% calcium chloride and 0.52% dopamine.